Experiences of human resource practitioners in managing workplace bullying - Mayne, Sarah (My University, 2021)
Workplace Bullying (WPB) is a counterproductive work behaviour which has been illustrated through decades of research to have detrimental effects on the well-being of targets, bystanders and organisations as whole. It is therefore of paramount importance that WPB is managed effectively by Human Resource Practitioners (HRPs) who are tasked to investigate and resolve this counterproductive behaviour. Limited studies, however, have considered HRPs voices in managing WPB. This is highly problematic as in order to effectively resolve WPB incidents which emerge, it is important to understand the challenges and experiences of those tasked to manage it. Further to the above, this study was conducted during the COVID 19 pandemic and the research therefore explored the potentially new experiences and challenges of HRPs when managing WPB within a workforce who are working from home (WFH). To the researcher’s knowledge, no research has explored the above stated area. Considering the above, the present study utilised Ulrich’s multiple roles model as a theoretical approach to contextualise and gain a more in-depth understanding of the challenges HRPs face when managing WPB. This study used a qualitative research method and used face to-face, semi-structured interviews to collect data. Nine HRPs from a large organisation within Gauteng were interviewed and a thematic content analysis (TCA) was used to analyse the data collected. The main findings of this study indicated that HRPs often find themselves divided as they have to adopt the role of a strategic partner or the role of an employee champion when managing WPB, thus leaving HRPs unable to address the needs of both the organisation and employees in WPB incidents. HRPs further felt that their subordinate power position, higher level managers determining outcomes of bullying incidents, the lack of a bullying policy, the organisation’s highly competitive environment, autocratic and toxic leadership styles, and managers’ lack of people skills were their main challenges that impeded their ability to mitigate WPB. Further to the above, HRPs face new forms of bullying and new challenges when managing a remote workforce, namely cyberbullying, through the use of harsh tone, the merging of work and home life leaving employees without rest, insensitivity to employee’s home contexts, and micromanagement. The emergence of these new challenges and forms of bullying under COVID-19 conditions were discussed in accordance with the Job-Demands Control (JCD) Model to account for how COVID-19 conditions have created a fertile ground for the emergence of WPB. The implications of the study’s findings are that they contribute to the awareness of the traditional challenges facing HRPs when managing WPB within South African organisations, 5 as well as bring awareness to new forms of bullying HRPs are tasked to manage within a work environment when employees are WFH. This study’s findings may encourage organisations in traditional work environments to develop a comprehensive WPB policy which empowers HRPs to better manage WPB incidents both in face to face and WFH situations. This empowerment may enable HRPs to better manage WPB when powerful organisational members are involved, as well as enable them to better meet the needs of both management and employees in WPB incidents as they adopt the role of a change agent. Moreover, organisations are encouraged to provide managers with leadership training as well as people skills training which may serve to lower the number of WPB incidents which arise within the organisation. This research may further encourage organisations who have successfully had staff WFH to adopt flexible working hours and focus attention on outputs of employees rather than enforced hours ‘present’ at the office. Lastly, organisations need to establish a more supportive work environment during the COVID-19 pandemic which is cognisant of employee needs, their ability to manage work-home boundaries and their long-term safety concerns.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Arts by Coursework and Research Report in Organisational Psychology to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2021